Environmental blue light prevents stress in the fish Nile tilapia - Volpato, Gilson Luiz [UNESP]; Barreto, R.E. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2001)
The present study aimed to test the effects of blue, green or white light on the stress response of the Nile tilapia, Oreochromis niloticus (L.). Each color was tested on two groups of isolated adult Nile tilapia (8 replicates each): one being subjected to confinement stress, and the other not (control). A different environmental color was imposed on each compartment by covering the light source with cellophane of the respective color (green or blue; no cellophane was used for white light). The intensity of green, white and blue lights was 250, 590 and 250 lux, respectively. Basal plasma cortisol levels were determined for each fish prior to the experimental procedures. The fish were confined by being displaced toward one side of the aquarium using an opaque partition for 1 h both in the morning and the afternoon of the two consecutive days of the test. At the end of this 48-h period, plasma cortisol levels were measured again. Basal cortisol levels (ng/ml) were similar for each group (ANOVA, F(2;42) = 0.77, P = 0.47). Thus, plasma cortisol levels were analyzed in terms of variation from their respective basal level. After confinement, plasma cortisol levels were not increased in fish submitted to a blue light environment. Thus, blue light prevents the confinement-induced cortisol response, an effect not necessarily related to light intensity.
Keywords: stress; animal welfare; light color; cortisol; Nile tilapia; Oreochromis niloticus (L.)